Installation of Bored Piles with a Protective Silicate Shell of a New Design in Saline Silty-Clayey Soils - Bulat B. Unaibayev; Bulat Zh. Unaibayev; Nurgul Alibekova; Assel Sarsembayeva (Applied Sciences, 2021)
Designing advanced methods of corrosion protection and increasing the bearing capacity of pile foundations on saline clayey soils is a priority geotechnical task in Kazakhstan. The formation of a suffusion-resistant waterproof shell was achieved by silicatization of a borehole before concreting, by the installation of a mold into the borehole and the impregnation of a sodium silicate solution into the space between the mold and the soil under pressure. After coagulation of the silicate solution, the mold was removed and the formed shell was filled with corrosion-resistant concrete. Full-scale static pile load tests were conducted in the construction site “Retaining wall on Mount Koktobe” in Almaty. The bearing capacity of the piles with the protective silicate shell exceeded the bearing capacity of an ordinary pile by 2.5 times on average without wetting the site, and 3.2 times after prolonged wetting. The numerical model had a close relationship with the average experimental curve obtained when conducting six static pile load tests with the protective shell. A large economic effect of the developed piling technology with a protective shell was achieved, with a significant reduction in the cost of piling, equal to 27.85%.